2021
DOI: 10.1016/j.ajic.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hand hygiene audit in COVID intensive care units in a tertiary care hospital in South India

Abstract: Background: In the era of COVID-19 pandemic, there is an upsurge of healthcare-associated infections (HAI) in COVID intensive care units (ICUs), which can be reduced by following proper hand hygiene (HH) practice. Performing HH auditing in COVID ICU and providing timely feedback to the stake holders is crucial to reduce HAIs. Methods: From November 2020-April 2021, HH audit was conducted in COVID ICUs. HH complete adherence rate (HHCAR), HH partial adherence rate (HHPAR) and HH total adherence rate (HHTAR) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 The list of excluded studies and reasons for exclusion are shown in Figure 1 . Among the ten included studies, six studies were carried out in China 26 , 27 , 28 , 29 , 32 , 33 , one in America 30 , one in Germany 31 , one in Italy 34 and one in India 35 , including three cross-sectional surveys 27 , 28 , 32 , six before-after studies 29 , 30 , 31 , 33 , 34 , 35 , and one randomized controlled trial (RCT) study. 26 All the studies were conducted between December, 2019 and April, 2021, and the HHC rates ranged from 46% to 100% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 The list of excluded studies and reasons for exclusion are shown in Figure 1 . Among the ten included studies, six studies were carried out in China 26 , 27 , 28 , 29 , 32 , 33 , one in America 30 , one in Germany 31 , one in Italy 34 and one in India 35 , including three cross-sectional surveys 27 , 28 , 32 , six before-after studies 29 , 30 , 31 , 33 , 34 , 35 , and one randomized controlled trial (RCT) study. 26 All the studies were conducted between December, 2019 and April, 2021, and the HHC rates ranged from 46% to 100% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were performed in designated COVID-19 hospitals or wards. 26 , 28 , 32 , 33 , 35 Most of the studies (6/10) took the hospital as the whole unit to conduct the overall study. 29 , 30 , 31 , 32 , 33 , 34 Among all the healthcare providers included, 64 (48.85%) worked in ICU, accounting for the vast majority, followed by 46 (35.11%) in surgery and 21 (16.03%) in internal medicine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations